Essays on sustainable operations management - Preethi, Kulasekara Manavala Ramanujam (Nanyang Technological University, 2024)
The thesis presents three essays that address key challenges in sustainable operations management, focusing on internal carbon pricing, circular economy through leasing and remanufacturing, and inventory policy under a hybrid on-supply production setting. Each essay offers insights into balancing environmental sustainability with profitability in different context. The first essay was motivated by the increased adoption of internal carbon prices observed in our meetings with Singapore's Carbon Pricing Leadership Coalition. The internal carbon tax is a tax imposed by a firm on its business divisions based on the amount of emissions. The results show that a uniform carbon tax can maximize profits while meeting emissions targets. However, it may lead to the premature closure of some carbon-dependent SBUs with high abatement costs. A non-uniform tax design, however, preserves SBU viability, allowing gradual decarbonization. Although the firm may lose short-term profits, we show that such SBUs thrive and generate sufficient revenue when faced with an external carbon tax in the future that affects all firms in the market. The second essay addresses the ongoing debate on the merits of a circular economy business model: Leasing, particularly its profitability and environmental impact compared to selling. The study uses a discrete-time, infinite-horizon game to assess the joint adoption of leasing along with remanufacturing. Our findings suggest that higher disposal costs under stricter regulations can make remanufacturing and remarketing more appealing for leasing firms. Using computational experiments, we illustrate that, for a wide range of parameters, the desired region or the space in which leasing proves both more profitable and environmentally superior to selling becomes larger when remanufacturing is considered. We investigate the inventory control and production-scheduling decisions of a firm that is transitioning towards electrification of its production process. We consider a firm that relies on a hybrid setup to handle supply intermittency: a central facility powered by traditional non-renewable sources of energy and a dedicated local on-supply facility that produces a single chemical product using excess renewable energy generated on-site. Under a deterministic setting, we derive an optimal on-supply inventory policy that minimizes the firm's total costs. Using computational experiments and analytical results, we discuss the conditions in which the hybrid on-supply model outperforms fully centralized production. We further extend the analysis to consider stochastic demand and local supply.